Pengaruh Kinerja Keuangan Terhadap Nilai Perusahaan dengan Kebijakan Dividen sebagai Variabel Moderating pada Perusahaan Makanan dan Minuman yang Terdaftar pada Indeks Saham Syariah Indonesia - Azizah, Jihan Nur; Lating, Ade Irma Suryani; Muflihin, Mohammad Dliyaul; Salsabila, Shofiyah Nugraha; Susanto, Febry Fabian (JES (Jurnal Ekonomi Syariah), 2025)
This study aims to analyze the effect of financial performance on firm value in the food and beverage sector listed on the Sharia Stock Index (ISSI) with dividend policy as a moderating variable. This study uses a quantitative approach with secondary data from 35 companies for the 2019-2021 period obtained from the Indonesia Stock Exchange (IDX) website. The variables studied include current ratio, return on assets, total asset turnover, and debt to equity ratio. The data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA). The results showed that the current ratio has no significant effect on firm value. Return on assets has a positive and significant effect on firm value. Total asset turnover has a negative and significant effect on firm value. Debt to equity ratio has a positive and significant effect on firm value. Dividend policy is able to moderate the effect of liquidity on firm value, and is able to moderate the effect of return on assets, total asset turnover, and debt to equity ratio on firm value.